Antibacterial Activity of n-Hexane Dragon’s Blood Resin Extract (Daemonorops draco wild Blume) from Bener Meriah, Aceh Province, Indonesia - Khairan, Khairan; Arini, Musfira; Idroes, Rinaldi; Awang, Khalijah; Jacob, Claus (Heca Sentra Analitika, 2023)
The dragon’s blood resin (Daemonorops draco wild Blume) has been used in folk medicine for pharmacological activities such as antimicrobial, antivirus, anti-inflammation, gastrointestinal disorders, blood circulation dysfunctions, antitumor, and cancer. This study was designated to evaluate the antibacterial activity of n-Hexane dragon’s blood resin extract against Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, and Candida albicans 10231. The other purpose of this study was to determine the secondary metabolites compound of n-Hexane dragon’s blood resin extract. The antimicrobial activities of the n-Hexane dragon’s blood resin extract was determined using well diffusion method and the results showed that the extract at concentration of 15% exhibited antimicrobial activities against Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, and Candida albicans 10231 with the diameter inhibition of 13.20 mm; 21.3 mm; and 13.0 mm respectively. The phytochemicals screening showed that the extract contains secondary metabolites in the form of flavonoids. The GC-MS analysis showed that n-Hexane dragon’s blood resin extract contains 48 chemicals compounds, and the compound at RT 26 was indicated a Drachorhodin compound (C17H 18O3) with the mass ration of m/z was 270 g/mol. Overall, the n-Hexane dragon’s blood resin extract be a good choice for antimicrobial agent against bacteria and fungi.